Product Placement in Virtual Reality Videos from the Perspective of Dialogic Engagement. Issue 2 (4th May 2019) - Chen, Huan; Wang, Ye
Abstract: Two studies were conducted to examine product placement in virtual reality (VR) videos using the theoretical framework of dialogic engagement. Specifically, Study 1 used content analysis to investigate VR films on YouTube, and Study 2 applied a phenomenological approach to explore young consumers' responses to this innovative promotional tool. Findings revealed that while, in general, greater interactivity and dynamicity are more desirable to achieve a higher level of engagement, a balance between interactivity, dynamicity, subtlety, and prominence should be achieved to bridge the gap between product placement practices and audience's perceptions.